Pedagogical translanguaging : theoretical, methodological and empirical perspectives - Juvonen, Päivi; Juvonen, Päivi; Källkvist, Marie; Källkvist, Marie (Bilingual Education & Bilingualism ;, 2021)
This book presents cutting-edge qualitative case-study research across a range of educational contexts, as well as theory-oriented chapters by distinguished multilingual education scholars, which take stock of the field of translanguaging in relation to the education of multilingual individuals in today's globalized world.